R&D, Spillovers, Innovation Systems and the Genesis of Regional Growth in Europe - Andres Rodriguez-Pose; Riccardo Crescenzi (European Regional Science Association (ERSA), 2006)
The paper aims at understanding the balance between "endogenous" factors and "external" knowledge flows in the process of innovation and growth of EU regions. Research on the impact of innovation on regional economic performance in Europe has fundamentally followed three approaches: a) the analysis of the link between investment in R&D, patents, and economic growth; b) the examination of geographical diffusion of regional knowledge spillovers; and c) the study of the existence and efficiency of regional innovation systems. These complementary approaches have, however, rarely been combined. Important operational and methodological barriers have thwarted any potential cross-fertilization. In this paper, we try to fill this gap in the literature by combining in one model R&D, spillovers, and innovation systems approaches. A multiple regression analysis approach is conducted for all regions of the EU-25, including measures of R&D investment, proxies for socio-economic structure, for each region and in neighbouring regions. The empirical results highlight how the three above-mentioned factors interact with one another uncovering the importance not only of "endogenous"innovative efforts but also of local socio-economic conditions for the genesis and assimilation of innovation and its transformation it into economic growth across European regions. In addition, the quantitative analysis shows the importance of proximity for the transmission of economically productive knowledge.
Keywords: 330